Seismic response evaluation of the linked column frame system. (12th September 2012) - Malakoutian, Mohammad; Berman, Jeffrey W.; Dusicka, Peter
SUMMARY The linked column frame (LCF) system is proposed as a seismic load resisting system that uses conventional components to limit seismic damage to relatively easily replaced elements. The LCF features a primary lateral system, denoted the linked column, which is made up of dual columns connected with replaceable links, and a secondary flexible moment frame system with beams having fully restrained connections at one end and simple connections at the other. The linked columns are designed to limit seismic forces and provide energy dissipation via link yielding, while preventing damage to the moment frame under certain earthquake hazard levels. A design procedure is proposed that ensures plastic hinges develop in the links of the linked columns at a significantly lower story drift than when plastic hinges develop in the moment frame beams. The large drift difference helps enable design of this system for two distinct performance states: rapid return to occupancy, where only link damage occurs and relatively simple link replacement is possible, and collapse prevention, where both the links and the beams of the moment frame may be damaged. A series of 3‐story, 6‐story, and 9‐story prototype LCF buildings were designed using the proposed design approach. Nonlinear models were developed for the designs with the link models validated using recent experimental results. The seismic response of these systems was investigated for ground motions representing various seismic hazard levels. Results show that the LCF system not only provides collapse prevention, but also has the capability of limiting economic loss by reducing structural damage and allowing for rapid return to occupancy following earthquakes with shorter return periods. Copyright © 2012 John Wiley & Sons, Ltd.